Metode Pembelajaran Talking Stick Untuk Meningkatkan Keaktifan Belajar Siswa Kelas V Di SDN 6 Langkai Palangka Raya - Sapriline; Femmy Femmy; Novy Nurliyani (Sangkalemo : The Elementary School Teacher Education Journal, 2022)
This study aims to determine the increase in the learning activity of fifth grade students by applying the talking stick learning method. The research method used is Classroom Action Research (CAR) or Classroom Action Research which consists of 4 stages, namely planning, implementation, observation, and reflection. The research subjects were fifth grade students at SDN 6 Langkai Palangka Raya which consisted of 25 students. The research was conducted in 2 cycles, each cycle was carried out 3 times with data collection techniques using student activity observation sheets and field notes. The results showed that the application of the talking stick learning method can increase student learning activity, this is evidenced in the pre-cycle activities as a whole, the results of observations got an average score of 50.9, in the first cycle of meeting 1 it increased to 59.1, at the second meeting. increased to 65, at the 3rd meeting increased to 72.7. Furthermore, in the second cycle of meeting 1, student activity reached 79.8, the second meeting reached 84.7 and at the third meeting increased to 92.6 with a very good category. So that the increase from pre-cycle activities of 50.9 to the first cycle of 72.7 activities, there was an increase of 21.8 points. As for the activities of the first cycle of 72.7 to the activities of the second cycle of 92.6, there was an increase of 19.9 points. In addition, the success of the application of the talking stick learning method is influenced by the skills of the teacher in guiding students during learning, so that learning using the talking stick method feels fun. Thus, it can be concluded that the application of the talking stick learning method is proven to increase the learning activity of fifth grade students at SDN 6 Langkai Palangka Raya.